Landslide monitoring at both large and detailed scales using satellite A-DInSAR in Southern Lazio (italy) - Antonielli, Benedetta; Caprari, Patrizia; Marmoni, Gian Marco; Marini, Roberta; Di Renzo, Maria Elena; Giordano, Alessandro; Di Sora, Francesco; Vescovi, Giorgio; Mazzanti, Paolo; Bozzano, Francesca (Italian journal of engineering geology and environment, 2024)
The specific aim of this work has been exploiting satellite Advanced Differential SAR Interferometry (A-DInSAR) big data through the implementation of methodologies that can provide new insights into the identification of unknown landslides and the update of the inventoried landslides, at two different levels of detail: regional and slope scales. In particular, the slopescale studies are aimed at investigating the landslide processes that pose the greater risk of interfering with roads and inhabited zones, using both multisource A-DInSAR velocity measurements, geomorphological evidence, and surveys of damage to buildings or infrastructure. This multiparametric evaluation allows the update of the state and styles of activity and the landslide perimeters. In this paper, we provide a general overview of the method that works for regional scale analysis, with a focus on 3 case studies located in the Frosinone province (Central Italy), that have been investigated at a slope scale. Such cases concern slow-moving landslides such as complex, slow flow, or roto-translation mechanisms, featured by shallow or moderate depth and extension. The presented results pointed out that A-DInSAR big data can provide an update of the state of knowledge of active slope movements at a regional scale and can drive detailed studies with high-resolution data and onsite surveys to assess the hazard scenarios.